Renal Function Profiles in Preterm Neonates With Birth Asphyxia Within the First 24 H of Life - Zhang, Yu; Zeng, Hui-Hui (Frontiers in Pediatrics, 2020)
The characteristics of early renal function in preterm neonates of different gestational ages (GAs) with birth asphyxia (BA) remain unclear. Kidneys are sensitive to oxygen deprivation, and renal insufficiency may occur within 24 hours of BA. We aimed to elucidate the renal function profiles within the first 24 hours after the development of BA among vulnerable preterm neonates of different GAs. The medical records of 128 preterm neonates born to mothers with normal renal function were retrospectively analyzed. Data regarding the serum creatinine (SCr) and urea nitrogen (BUN) levels in venous blood, estimated creatinine clearance (eCCI) within the first hours after birth, and urinary output (UOP) in the first 24 hours after birth were compared between the preterm with BA population and GA-matched population without BA (n=64 and n=64, respectively). Significantly higher SCr levels and lower eCCI were observed in mid-late preterm neonates with BA than in preterm neonates without BA (84.05 versus [vs.] 64.20 µmol/L, z=4.41, p <0.001; 15.02 vs. 21.30 mL/min/1.73 m2, z=3.57, p <0.001, respectively). Very preterm neonates showed a higher UOP (2.01 vs. 1.66 mL/kg/h, z=2.01, p=0.045) after the development of BA than before. In preterm neonates with BA, the incidence of SCr >133 μmol/L, CCI <16 mL/min/1.73 m2 and UOP <1.0 ml/kg/h, was 10.94%, 62.50%, and 20.31%, respectively. Within 24 hours after birth, BA was associated with eCCI <16 mL/min/1.73 m2 (p=0.016, odds ratio=2.83, 95% confidence interval: 1.210-6.613) in preterm neonates. Different renal function profiles were observed in preterm neonates of different GAs within the first 24 hours of life after the development of BA. Candidate therapies based on different renal function statuses will bring these vulnerable patient populations of different GAs closer to receiving precision medicine.